FAKTOR RISIKO HYGIENE PERORANGAN SANTRI TERHADAP KEJADIAN PENYAKIT KULIT SKABIES DI PESANTREN AL-BAQIYATUSHSHALIHAT TANJUNG JABUNG BARAT TAHUN 2017 - Parman Parman; Hamdani Hamdani; Irwandi Rachman; Angga Pratama (Universitas Batanghari Jambi, 2017)
Background: Scabies incident at boarding school Al-Baqiyatushshalihat Tanjung Jabung West in 2015-2016 there are 200 cases. The aim of this study is the relationship of individual hygiene students with the incidence of skin diseases of skabies in Pesantren Al-Baqiyatushshalihat Tanjung Jabung Barat Year 2017. Method: This research is a quantitative research with case control approach Data collection method is done by distributing questioner then analyzed by Univariat and Bivariat. The case population in this study is all santri who suffer from scabies in Al-Baqiyatushship Pesantren in 2017. The control population is santri who do not suffer from scabies in Al-Baqiyatushshalihat boarding school. Sampling method using total sampling method. Data were analyzed univariat and bivariate with chi-square test. Result: The results showed that there was a correlation between skin hygiene (p-value = 0,004; OR = 3,125; 95% CI = 1,943-6,542), hand hygiene and nail (p-value = 0,001; OR = 3,473; 95% CI = 1,669-7,225), genital hygiene (p-value = 0,002; OR = 3,762; 95% CI = 1,668-8,574), clothing hygiene (p-value = 0,000; OR = 4,062; 95% CI = 1,926-8,571), hygiene (p-value = 0.000; OR = 4,316; 95% CI = 2,045-9,108), cleanliness of bed and bed linen (p-value = 0,000; OR = 13,895; 95% CI = 5,721-33,747) with incidence of Scabies Skin Disease in Al-Baqiyatushshalihat Pesantren Tanjung Jabung Barat. Conclusion: Personal hygiene is a risk factor for scabies events. Bed and bedding hygiene is the highest risk variable for the incidence of scabies. Keywords: Scabies incident, individual hygiene